2019
DOI: 10.1111/imr.12818
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reactivity on a spectrum: A sliding scale of peripheral B cell tolerance

Abstract: Efficient mechanisms of central tolerance, including receptor editing and deletion, prevent highly self-reactive B cell receptors (BCRs) from populating the periphery.Despite this, modest self-reactivity persists in (and may even be actively selected into) the mature B cell repertoire. In this review, we discuss new insights into mechanisms of peripheral B cell tolerance that restrain mature B cells from mounting inappropriate responses to endogenous antigens, and place recent work into historical context. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 165 publications
(310 reference statements)
1
66
0
Order By: Relevance
“…Even in non-autoimmune prone genetic backgrounds, some aspects of deletion, developmental arrest and anergy may be overcome by augmenting anti-apoptotic pathways (23) or by provision of T cell help (24) and innate stimuli (25). While these have been informative, the typical readouts for these experiments are technically limited and include the tracking of BCR-transgenic cells and/or indirect probing for the frequency of self-reactive BCRs by cloning and screening them as recombinant antibodies by ELISA (26). Whether these readouts directly reflect ongoing autoreactivity by a physiological repertoire remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in non-autoimmune prone genetic backgrounds, some aspects of deletion, developmental arrest and anergy may be overcome by augmenting anti-apoptotic pathways (23) or by provision of T cell help (24) and innate stimuli (25). While these have been informative, the typical readouts for these experiments are technically limited and include the tracking of BCR-transgenic cells and/or indirect probing for the frequency of self-reactive BCRs by cloning and screening them as recombinant antibodies by ELISA (26). Whether these readouts directly reflect ongoing autoreactivity by a physiological repertoire remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic sensing of self-antigen in the periphery enforces an anergy transcriptional program (10,27) and the downregulation of surface IgM (26). The two key goals of this are 1) dampening signal transduction via the BCR upon self-ligation and 2) reducing the probability of encountering T cell help.…”
Section: Discussionmentioning
confidence: 99%
“…We previously characterized a fluorescent reporter of Nr4a1 expression (NUR77-EGFP BAC Tg) that scales with the extent of Ag stimulation in vitro and in vivo, and therefore serves to mark naturally occurring autoreactive T and B cells in healthy mice [22][23][24][25][26] . We showed that this reporter correlates with self-reactivity in three different BCR Tg models 25,[27][28][29] . More recently, we have identified a role for NUR77/Nr4a1 in imposing a novel layer of B cell tolerance in vivo by mediating competitive elimination of chronically Ag-stimulated self-reactive B cells in settings with a limiting supply of the B cell survival factor BAFF 28 .…”
Section: Introductionmentioning
confidence: 86%
“…cells acutely activated only by Ag are normally restrained, and helps to enforce their dependence upon co-stimulation. Indeed, we have previously identified upregulation of NUR77-EGFP expression in self-reactive B cells in response to chronic BCR engagement, and isolated a specific role for NUR77 in restricting the survival of such cells, particular in settings where the B cell survival factor BAFF is limiting25,[27][28][29] . It has been proposed that certain features of anergic B cells, including reduced half-life, may be understood in part as a "special case" of the acute B cell response to signal 1 in the absence of signal 266 .…”
mentioning
confidence: 99%
“…Fas) also limit the effector function of autoreactive B cells. Mutations in those additional tolerance checkpoints would permit less stringent control of these anergic B cells [22,29]. Evidence of this can be drawn from neutralising antibodies against HIV which are isolated from hosts with 'relaxed' B cell tolerance and often originate from germline autoreactive precursors [30].…”
Section: Recent Studies On Deletional Tolerance In T Cells Report Anamentioning
confidence: 99%